Secrets of the Lean Plate Club: A Simple Step-by-Step Program to Help You Shed Pounds and Keep Them Off for Good - Squires, Sally (New York St. Martins Press, 2006)
Draws on the ancient Indian system of medicine called Ayurveda, and Western scientific research, to offer specific strategies for permanent weight loss. By understanding the interaction between mind and body Dr Chopra shows that you can lose weight successfully without the pressure of dieting.
Include Illustration, Index
Keywords: Weight loss -- Medicine, Ayurvedic -- Mind and body